Obesity and its Measurement in a Community-Based Sample of Women with Systemic Lupus Erythematosus - Katz, Patricia (2011)
OBJECTIVE: To determine the prevalence of obesity and evaluate how accurately standard anthropometric measures identify obesity among women with SLE. METHODS: Dual-energy x-ray absorptiometry (DEXA), height, weight, and waist and hip circumference were collected from 145 women with SLE. Three anthropometric proxies of obesity (body mass index (BMI) ≥30 kg/m(2), waist circumference (WC) ≥88 cm, and waist-hip ratio (WHR) ≥0.85) were compared to a DEXA-based obesity criterion. Correspondence between measures was assessed with Cohen’s kappa. Receiver operating characteristic (ROC) curves determined optimal cut-points for each anthropometric measure, relative to DEXA. Framingham cardiovascular risk scores were compared among women who were classified as not obese by both traditional and revised anthropometric definitions, obese by both definitions, and obese only by the revised definition. RESULTS: 28%, 29%, 41%, and 50% were classified as obese by WC, BMI, WHR, and DEXA, respectively. Correspondence between anthropometric and DEXA-based measures was moderate. Women misclassified by anthropometric measures had less truncal fat and more appendicular lean and fat mass. Cut-points were identified for anthropometric measures to better approximate DEXA estimates of percent body fat: BMI ≥26.8 kg/m(2), waist circumference ≥84.75 cm., and waist-hip ratio ≥0.80. Framingham risk scores were significantly higher in women classified as obese by either traditional or revised criteria. CONCLUSIONS: A large percentage of this group of women with SLE was obese. Substantial portions of women were misclassified by anthropometric measures. Utility of revised cut-points compared to traditional cut-points in identifying risk of cardiovascular disease or disability remains to be examined in prospective studies, but results from the Framingham risk score analysis suggest that traditional cut-points exclude a significant number of at-risk women with SLE.